Odpowiedzi

2009-11-18T00:20:46+01:00
X3-2x2-9x+18=0
x2(x-2)-9(x-2)=0 wyciągasz czynnik przed nawias
(x2-9)(x-2)=0 grupujesz
(x-3)(x-3)(x-2)=0
x=3 x=2



1 1 1
Najlepsza Odpowiedź!
2009-11-18T00:22:33+01:00
A) x³-2x²-9x+18=0

x²(x-2) -9(x-2)=0

(x²-9)(x-2)=0

(x-3)(x+3)(x-2)=0

Rozwiązania to 2,3,-3

b)243x²-1=0

(9√3x-1)(9√3+1)=0

rozwiązania to:

9√3x=1
x=1/9√3
x=√3/27

oraz

9√3x=-1
x=-1/9√3
x=-√3/27
1 4 1
2009-11-18T00:24:06+01:00
A]x³-2x²-9x+18=0,czyli x²(x-2)-9(x-2)=0,więc:(x²-9)(x-2)=0→x²=9→x₁=3,x₂=[-3],x₃=2 zad.b]243x²-1=0,czyli Δ=b²-4ac=0+972=972,,,√Δ=√972=√324×3→√Δ=18√3 więc:x₁=-b-√Δ:2a=-18√3:486=-1/27√3 lub x₂=1/27√3
2 2 2